1994
DOI: 10.1002/1097-0142(19940115)73:2<483::aid-cncr2820730238>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of primary or relapsing limb cancer by isolation perfusion with high-dose alpha-tumor necrosis factor, gamma-interferon, and melphalan

Abstract: Background. Utilization of alpha‐tumor necrosis factor (α‐TNF) in clinical practice is limited by severe general side effects. Very promising results with low toxicity were reported with administration of α‐TNF by isolation perfusion in extracorporeal circulation. Methods. From December 1991 to November 1992, 14 patients underwent perfusion with α‐TNF (2–4 mg, total dose), gamma‐interferon (1.5 × 106 IU), and melphalan (10 mg/1/perfused limb). Twelve patients presented intransit metastases of the limbs, one pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
16
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(20 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…5,25,26 These changes were mainly characterized by acute circulatory failure mimicking septic shock (best called Systemic Inflammatory Response Syndrome 27 ), which was associated with disturbances of gas exchanges, decreases in blood cell counts, and abnormal liver function test results. 5,25,26,28 This condition required aggressive supportive therapy, including fluid resuscitation, administration of vasopressors and inotropic agents immediately after TNF-␣ administration, and respiratory assistance. 25,28,29 Major preventive measures needed to be taken in those series to diminish severe complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,25,26 These changes were mainly characterized by acute circulatory failure mimicking septic shock (best called Systemic Inflammatory Response Syndrome 27 ), which was associated with disturbances of gas exchanges, decreases in blood cell counts, and abnormal liver function test results. 5,25,26,28 This condition required aggressive supportive therapy, including fluid resuscitation, administration of vasopressors and inotropic agents immediately after TNF-␣ administration, and respiratory assistance. 25,28,29 Major preventive measures needed to be taken in those series to diminish severe complications.…”
Section: Discussionmentioning
confidence: 99%
“…25,28,29 Major preventive measures needed to be taken in those series to diminish severe complications. 25,26,30 A pulmonary (Swan-Ganz) catheter was installed before the procedure, and dopamine infusion (3 mg/kg/minute) was started just before the administration of TNF-␣. 25,26 The pulmonary side effects consisted of alterations in the delivery and uptake of oxygen, with reduced oxygen extraction, for 24 to 48 hours.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficacy of the application of TNF in combination with cytostatic agents in ILP for the treatment of patients with in-transit melanoma metastases or locally advanced soft tissue sarcomas has now been well established. [1][2][3] This treatment can be used as a limb-sparing neoadjuvant therapy when it is followed by local excision of residual tumor. TNF became a registered cancer drug in Europe on the basis of results obtained in multicenter studies in which clinical response rates of 75% and limb salvage rates of 71% were observed in 196 patients who had been classified as having unresectable tumors that could have been managed only by amputation.…”
mentioning
confidence: 99%